PERFECT APPRAISAL : ALL YOU NEED TO GET IT RIGHT THE FIRST TIME - HUDSON, Howard (Random House Business Books LondonGB, 1999)
Advocates an appraisal process that is ongoing, collaborative and helping. Deals with topics including: setting objectives for appraisal meetings; identifying the most suitable time and place; deciding on what issues should be raised; and post-interview follow-up. Also includes guidelines on training for the perfect appraisal; and questions designed to help appraisees to identify areas for personal improvement.